Connecting Direct Effects of CO2 Radiative Forcing to Ocean Heat Uptake and Circulation. (10th July 2019) - Menzel, Molly E.; Merlis, Timothy M.
Abstract: The ocean's response to direct atmospheric effects of increased carbon dioxide's (CO2 ) radiative forcing is examined. These direct effects are defined as the climate changes that result from forcing on a fast time scale of about a year, independent of the slower surface warming that the forcing also provokes. To evaluate how these direct effects impact ocean heat uptake and circulation, output of atmospheric general circulation model (GCM) simulations are used to force an ocean GCM with comprehensive boundary conditions. Perturbation simulations with the prescribed response to a quadrupling of atmospheric CO2 include altered surface winds, freshwater fluxes, downwelling shortwave radiation, and downwelling longwave cloud radiative effect. The perturbation simulations show that the intensification and poleward shift of surface winds, particularly in the Southern Ocean, strengthen the shallow overturning circulation in the tropical Pacific and deep overturning in the Atlantic. This, in turn, has a cooling effect on the global ocean at shallow depths. A two‐layer energy balance model, designed to capture transient global mean climate change, is adapted to account for the altered ocean heat uptake from direct effects. The direct change in global mean ocean heat uptake is a decrease of about 0.3 W/m 2 for quadrupling of CO2, offsetting about 5% of the surface longwave forcing. Key Points: The direct effects of CO2 on the surface atmospheric fields that interact with the ocean are analyzed The influence of direct effects on ocean heat content and circulation in ocean general circulation model (GCM) simulations is assessed GCM results can be emulated by adapting two‐layer energy balance model of ocean heat uptake to include direct effects